2022
DOI: 10.32920/ihtp.v2i3.1656
|View full text |Cite
|
Sign up to set email alerts
|

Examining the quality of life of patients living with breast cancer in Southern Sri Lanka: A descriptive cross-sectional study

Abstract: Introduction: Globally breast cancer (BC) is the most common cancer among women and Sri Lanka is not an exception. Cancer influences the quality of life (QoL) of cancer patients. The survival rates and the QoL of BC patients have improved significantly over the last few decades. However, factors associated with the QoL of patients with BC have not been well studied in Sri Lanka. The aim of the study was to assess the QoL and its correlates among patients with BC treated at a tertiary care hospital in Southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Younger women experience more psychological morbidity and lower QoL after breast cancer diagnosis than older women, as older patients are believed to have greater social and emotional functioning, which has been associated with better QoL, while younger patients have poor adjustment, intolerable treatment, less coping, and significant distress. 14 In the present study, female patients had the lowest mean social function score among the five function scales, indicating poor social support for women in the family and society. Studies from Saudi Arabia and Malaysia revealed that social support from family and society improved the general QoL for female breast cancer patients.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Younger women experience more psychological morbidity and lower QoL after breast cancer diagnosis than older women, as older patients are believed to have greater social and emotional functioning, which has been associated with better QoL, while younger patients have poor adjustment, intolerable treatment, less coping, and significant distress. 14 In the present study, female patients had the lowest mean social function score among the five function scales, indicating poor social support for women in the family and society. Studies from Saudi Arabia and Malaysia revealed that social support from family and society improved the general QoL for female breast cancer patients.…”
Section: Discussionmentioning
confidence: 44%
“…However, in women, functional scores in the advancing age group improved compared to the 18–39‐year age group, indicating that women cope better than men as age advances. Younger women experience more psychological morbidity and lower QoL after breast cancer diagnosis than older women, as older patients are believed to have greater social and emotional functioning, which has been associated with better QoL, while younger patients have poor adjustment, intolerable treatment, less coping, and significant distress 14 . In the present study, female patients had the lowest mean social function score among the five function scales, indicating poor social support for women in the family and society.…”
Section: Discussionmentioning
confidence: 51%
“…Data on SS and the impact of SS on patients with cancer are scarce in the Sri Lankan setting. According to the previous publication by us, cancer patients had obtained higher family support (21) and family support was one of the significant predictors of QoL among patients with cancer (21,22). According to the findings of patients with cancer in the Sri Lankan context, some had reported a high prevalence of psychological distress (21) and clinical depression (23) which could be reduced by providing SS.…”
Section: Introductionmentioning
confidence: 93%
“…According to the previous publication by us, cancer patients had obtained higher family support (21) and family support was one of the significant predictors of QoL among patients with cancer (21,22). According to the findings of patients with cancer in the Sri Lankan context, some had reported a high prevalence of psychological distress (21) and clinical depression (23) which could be reduced by providing SS. A few studies had reported SS on different clinical and non-clinical samples (e.g., patients with chronic kidney disease (CKD), elders, etc.)…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation